2011
DOI: 10.1503/cjs.041209
|View full text |Cite
|
Sign up to set email alerts
|

Early results of a Canadian laparoscopic sleeve gastrectomy experience

Abstract: Background: Sleeve gastrectomy (SG) is a relatively new bariatric procedure with a number of advantages compared with Roux-en-Y gastric bypass. However, SG also has a number of disadvantages and associated risks. We sought to examine perioperative complications and outcomes of laparoscopic SG (LSG) in a single major Canadian bariatric surgery centre (Victoria, BC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 17 publications
0
11
0
5
Order By: Relevance
“…A number of bariatric centres across Canada have adopted programs for early detection of staple line leaks, 22,23 whereas others have decided to discontinue the use of routine contrast studies and have chosen to order imaging only when clinically indicated. 24 These imaging studies usually involve a routine Gastrografin swallow study on POD1. This has also been the practice at our centre, where LSG accounts for 98% of the procedures performed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of bariatric centres across Canada have adopted programs for early detection of staple line leaks, 22,23 whereas others have decided to discontinue the use of routine contrast studies and have chosen to order imaging only when clinically indicated. 24 These imaging studies usually involve a routine Gastrografin swallow study on POD1. This has also been the practice at our centre, where LSG accounts for 98% of the procedures performed.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,18,19 Contudo, o tempo de follow-up destes doentes é ainda relativamente curto (mínimo de 18 meses, máximo de 46 meses), sendo que seria fundamental manter o acompanhamento dos doentes de forma a analisar a evolução ao longo do tempo -existe inclusivamente um artigo que refere que a resolução da diabetes mellitus tipo 2 é três vezes mais frequente aos 10 anos comparativamente a métodos de intervenção não cirúrgicos.…”
Section: Discussionunclassified
“…A literatura demonstra que existe uma melhoria significativa no que concerne a esta patologia após a realização de cirurgia bariátrica. 6,11,18,19 A literatura apoia também a hipótese de que os indiví-duos obesos, nomeadamente os candidatos a cirurgia bariátrica, têm mais frequentemente patologia do foro psicológico/psiquiátrico relativamente a indivíduos não obesos; 20 a 60% dos doentes sofrem de doença psiquiátrica do eixo I, 20 sendo a depressão, a ansiedade e o binge eating disorder das patologias mais comuns. 8,12,16,21 Observa-se também uma associação entre fatores psicológicos e psicossociais, comportamento alimentar disfuncional e obesidade.…”
Section: 17unclassified
See 2 more Smart Citations